2001
DOI: 10.1037/0022-006x.69.5.814
|View full text |Cite
|
Sign up to set email alerts
|

One-session treatment of specific phobias in youths: A randomized clinical trial.

Abstract: Sixty children, ages 7-17 years, who fulfilled Diagnostic and Statistical Manual of Mental Disorders (4th ed.; American Psychiatric Association, 1994) diagnosis for various specific phobias were randomized to (a) 1-session exposure treatment alone, (b) 1-session treatment with a parent present, or (c) wait-list control group for 4 weeks. After the waiting period, the wait-list patients were rerandomized to the active treatments. The patients' phobias were assessed with behavioral approach tests (approach behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
2
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(155 citation statements)
references
References 38 publications
4
145
2
4
Order By: Relevance
“…More recent studies of psychological interventions for childhood anxiety (e.g., Barrett, Healy-Farrell, & March, 2004;Öst, Svensson, Hellström, & Lindwall, 2001), psychological interventions targeting constructs other than childhood anxiety (e.g., conduct problems; Sanders, Markie-Dadds, Tully, & Bor, 2000;Webster-Stratton & Hammond, 1997), and other forms of intervention (e.g., medication interventions for attention-deficit/hyperactivity disorder; Pearson et al, 2003;Pliszka, Browne, Olvera, & Wynne, 2000) convey the same point. Conclusions vary across outcome measures, methods of analysis, and measures purportedly assessing the constructs targeted for intervention.…”
Section: Within-study Inconsistenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies of psychological interventions for childhood anxiety (e.g., Barrett, Healy-Farrell, & March, 2004;Öst, Svensson, Hellström, & Lindwall, 2001), psychological interventions targeting constructs other than childhood anxiety (e.g., conduct problems; Sanders, Markie-Dadds, Tully, & Bor, 2000;Webster-Stratton & Hammond, 1997), and other forms of intervention (e.g., medication interventions for attention-deficit/hyperactivity disorder; Pearson et al, 2003;Pliszka, Browne, Olvera, & Wynne, 2000) convey the same point. Conclusions vary across outcome measures, methods of analysis, and measures purportedly assessing the constructs targeted for intervention.…”
Section: Within-study Inconsistenciesmentioning
confidence: 99%
“…Change can be examined using a number of sources, such as self-report, reports from significant others, use of performance-based or physiological measures, institutional records, and reports from independent laboratory observations (see Tables 7-10; Figure 2; Kazdin, 2003;Kendall, 1999). Indeed, multiple sources (e.g., parent, child, teacher, clinician, independent observer, physiological measurements) are employed in research examining interventions targeting constructs perceived as difficult to measure using methods other than self-assessments (e.g., childhood anxiety; Kendall, 1994;Barrett et al, 1996Barrett et al, ,2004Geller et al, 2001;Liebowitz et al, 2002;Öst et al, 2001). …”
mentioning
confidence: 99%
“…Fernandez, Storch, Lewin, Murphy & Geffken, 2006;Lewin et al, 2005;Savva & Rees, 2006;Whiteside, Brown & Abramowitz, 2008), specific phobia (e.g. Davis, Ollendick & Öst, 2009;Flatt & King, 2010;Öst, Svensson, Hellström & Lindwall, 2001), school refusal (Moffitt, Chorpita & Fernandez, 2004) and panic disorder with agoraphobia (Angelosante, Pincus, Whitton, Cheron & Pian, 2009). To date, only one study has investigated the potential usefulness of this approach with childhood SP.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It was noteworthy, though, these children reported significantly more fears than did children in the other three countries. In Sweden the reported results have been more contradictory, with two studies finding more fearfulness in girls (Kendler et al, 2008;Lichtenstein & Annas, 2000), but, in contrast, Svensson and Öst (2001) reported fearfulness not to differ between boys and girls, in Sweden. Explanations for the discrepancy could be the use of parental report of children's fears in some studies and the use of children's own report in others, the use of different instruments to measure fear, and the representativeness of the samples.…”
Section: Normal Development Of Fearsmentioning
confidence: 53%
“…One such instrument that has frequently been used to assess anxiety disorders in children is the Anxiety Disorders Interview Schedule for Children, child and parent versions (ADIS-C/P; Silverman & Albano, 1996). This instrument's popularity probably stems in part from reports of good to excellent test-retest reliability (Silverman, Saavedra, & Pina, 2001), and also good to excellent inter-rater reliability reports, outside the country of origin (Öst, Svensson, Hellström, & Lindwall, 2001). For the section on specific phobia, in the ADIS-C/P, children and parents are asked in separate interviews to rate fear and avoidance, and interference in the child's daily life, on a rating scale of 0-8 (with the aid of a visual analogue scale, pictured as a feelings thermometer).…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%